A novel telomere biology disease‐associated gastritis identified through a whole exome sequencing‐driven approach - Namrata Setia; Daniela delGaudio; Priscilla Kandikatla; Kelly Arndt; Melissa Tjota; Peng Wang; Jeremy Segal; Mir Alikhan; John Hart (Wiley, 2024)
Abstract A whole exome sequencing (WES)‐driven approach to uncover the etiology of unexplained inflammatory gastritides has been underutilized by surgical pathologists. Here, we discovered the pathobiology of an unusual chronic atrophic gastritis in two unrelated patients using this approach. The gastric biopsies were notable for an unusual pattern of gastritis with persistent dense inflammation, loss of both parietal and neuroendocrine cells in the oxyntic mucosa, and sparing of the antral mucosa. The patients were found to harbor pathogenic variants in telomeropathic genes (POT1 and DCLRE1B). Clonality testing for one of the patients showed evidence of evolving clonality of TCR‐gene rearrangement. Both patients showed significantly decreased numbers of stem/progenitor cells by immunohistochemistry, which appears to be responsible for the development of mucosal atrophy. No such cases of unusual chronic atrophic gastritis in the setting of telomeropathy have been previously reported. The loss of stem/progenitor cells suggests that stem/progenitor cell exhaustion in the setting of telomere dysfunction is the likely mechanism for development of this unusual chronic atrophic gastritis. The results underscore the need for close monitoring of these gastric lesions, with special regard to their neoplastic potential. This combined WES‐driven approach has promise to identify the cause and mechanism of other uncharacterized gastrointestinal inflammatory disorders.